(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Introduction: Globally, around 34 million people are living with HIV in 2010, and 35% of the pregnant women are tested for HIV in the low and middle income countries. HIV infection in pregnancy has become a complication of pregnancy in some developing countries. This has major implications for the management of pregnancy and birth. With an estimated one and a half million HIV-positive women becoming pregnant each year, almost 600,000 children will be infected by mother-to-child transmission annually. Methodology: A cross sectional study was conducted from October – December 2011 in the Department of Obstetrics and Gynecology, Khyber Teaching Hospital, Peshawar. It is a tertiary care hospital located in Peshawar. A sample of 200 pregnant females was used to accomplish the study. The targeted study population was all antenatal attendees who were visiting the hospital within the current pregnancy. A pre- coded, pre- tested structured questionnaire was used to gather information on the study variables. The questionnaire included variables related socio-demographics e.g., age, education status, occupation, residence. It also included the gestational age and gravidity of the pregnant females. Results: A total of 200 pregnant females attending the antenatal clinic participated in the study. The age range of the respondents was 17 to 45 years. Age range 17-25 years accounted for the highest percentage (52%). Around 70% of the respondents had no formal schooling while only 18% had got secondary education. Ninety – seven percent of the females were housewives while only 3% were employed. Out of the total respondents (200) only 86 (43%) have heard of HIV while 114 (57%) respondents have not heard of HIV. Conclusion: The study concluded that only 43% of the pregnant females have heard of HIV. Although this is not promising still there is room for improvement. Health education targeting pregnant females is essential. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 9-14 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7972